(untitled) (Heritage, 2025)
This study focuses on the transcription of the apocryphal text Isaiah’s Vision, dating from the early 16th century, preserved in the Bishop’s Office Book (Činovnik arhijerejski), manuscript no. 134 from the collection of the Dečani Monastery. The Vision appears as the final composition in the manuscript, though several sentences are missing at the end. The title and initial letter were left unwritten, with blank space reserved for their later addition in red ink. The name of the scribe remains unknown; the text was written in a semi-uncial script with elements of cursive. The language is Church Slavonic of the Serbian recension, with orthography characteristic of the Resava school. Inconsistencies are observed in the use of some letters. This transcription belongs to the first variant of the Vision and is preserved in four Serbian manuscripts, one of which is the Dečani copy. The narrative describes the ascension of the prophet Jeremiah to heaven, accompanied by an angel who reveals to him divine mysteries across the seven heavens. Upon completing his celestial journey, Jeremiah is instructed to return to earth and convey to the people all he has learned about the heavenly secrets. As no prior edition of this Vision exists, the remainder of the paper presents its full text based on the Dečani manuscript no. 134.